Letter (copy) : Invitation to British women to visit Spain - Tewson, Vincent
012a-0032-001 Secretary's. HVT/FC/EK/195. 3rd November, 1938. Mr. G. Stolz, International Federation of Trade Unions, 9, Avenue D'Orsay, PARIS VIIe. Dear Mr. Stolz, INVITATION TO BRITISH WOMEN TO VISIT SPAIN I thank you for your letter of the 2nd instant, from which I note the reply you have received from the U.G.T. regarding the Barcelona Liaison Committee and the Women's Groups in the Iron and Steel Trade Unions. Yours sincerely, Assistant Secretary. 292/946/12a/32